Bleb Needling Procedure in Juvenile Open Angle Glaucoma (JOAG) for Failed Bleb in Trabeculectomy: Poster Presentation - Case Report - General practitioner - Putri, Rizqi Suryani; Nuradianti, Lydia (Majalah Oftalmologi Indonesia, 2023)
Introduction : JOAG is less responsive to medications and often requires surgical therapy. The main choice of surgery is trabeculectomy. One of its success rates is determined by the formation of bleb. Failed bleb causes an increase in IOP. To repair the bleb, bleb needling can be performed as a simple procedure. Case Illustration : A 7-year-old boy came with a chief complaint of pain accompanied by redness of the left eye. The patient was diagnosed with JOAG and had underwent trabeculectomy with mitomycin-C (MMC) 3 months ago on the right eye and 2 months ago on the left eye with complete success surgery. On physical examination, intraocular pressure (IOP) was 12 mmHg / 29 mmHg with flat bleb on the left eye. Visual acuity on the right eye was 3/10 with cc C-2.00 X 0° ? 7/10 while on the left eye was light perception without possible refractive correction. Timolol maleate and latanoprost eye drops were given for 2 weeks but the IOP remained high. Therefore, the patient underwent bleb needling with 5- Fluorouracil (5-FU) on the left eye. Post-operatively, the IOP was 12 mmHg without antiglaucoma medication. Discussion : Failure of the trabeculectomy bleb can occur due to fibrotic proliferation as part of the wound healing response. Studies stated 5-FU bleb needling provide clinically significant IOP lowering and minimal complication. Reduced IOP post needling and formation of bleb indicate successful needling. Conclusion : Bleb is an important indicator of a success trabeculectomy surgery. Bleb needling with 5-FU could be considered as effective and safe procedure after trabeculectomy failure.